Penguatan Kompetensi Praktis Mahasiswa Pendidikan Biologi melalui Pelatihan Pembuatan Filter Air Sederhana - Anggun Maharani; Dimas Ridho; Ratna Sari Dewi; Aldo Geo Frengky Saragih; Delima Sianturi; Elsa Elperida Pandiangan; Monalisa Situmorang; Mei Sufi Anisa Sibarani; Wiranda Hasibuan; Lenni Khotimah Harahap (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Clean water is a fundamental necessity; however, many regions still struggle to access it due to contamination by suspended particles, organic matter, and harmful microorganisms. This activity aims to strengthen the practical competence of Biology Education students at Universitas Negeri Medan through training in making simple water filters. The training was conducted through demonstrations and simulations using turbid water from the Tembung River as a sample. The filter was constructed from readily available materials such as used plastic bottles, cotton, tissue, sand, small gravel, and palm fiber arranged in layers. The results showed that the filter effectively reduced water turbidity and enhanced students’ skills in clean water treatment technology. The training also encouraged students to develop 21st-century skills such as critical thinking, problem-solving, and collaboration, while preparing them as future educators capable of raising community awareness about the importance of maintaining water quality. Therefore, this training has the potential to be developed as an applicative environmental education model that contributes positively to clean water provision.